Ideación e Intento Suicida en Estudiantes de Nivel Medio Superior de la Universidad de Guanajuato - Chávez Hernández, Ana María; Pérez Hernández, Rosaura; Macías García, Luis Fernando; Páramo Castillo, Daniel (Acta Universitaria, 2004)
Ideation and suicide attempts are important pieces of the suicide behavior spectrum. Have both relative frequencies between adolescents because in this developmental stage many important social, familiar and psychological factors intervene. The present paper, part of a broader project in the same population, was aimed to identify the prevalence and associated factors to ideation and suicide attempts among high school students of University of Guanajuato. It was applied aquestionnaire to a two stages random sample (n=2 532), age range was 13 to 22 years old. Suicide ideation indicators were founded in almost a quarter of the sample, while 8.6 % have at least one suicide attempt, generally around the age of thirteen; motives for attempting suicide were mainly referred to interpersonal or affective aspects. Almost in every studied variable, women obtained the greater percentage. Suicide Ideation, as any other suicide act, is not an isolated event, but represents a serious risk at social and personal level, and its determination has to be found in a multiplicity of factors.
Keywords: Array; Array; Array